RESIDENTIAL FLOOR TILING AS A MATHEMATICAL MODELING CONTEXT FOR GEOMETRY LEARNING IN JUNIOR HIGH SCHOOL - Nasrum, Akbar; Marniati, Marniati (JME (Journal of Mathematics Education), 2025)
Mathematical modeling is a learning approach that emphasizes the connection between mathematical concepts and real-life situations. However, geometry instruction in junior high schools is still frequently presented in an abstract manner and lacks meaningful real-world contexts. This study aims to examine residential floor tiling as a mathematical modeling context for geometry learning at the junior high school level. The research was conducted using a subsidized house type 36 located in the Citra Latambaga Housing Complex, Latambaga District, Kolaka Regency, focusing on floor tiling activities involving various tile sizes and materials. A qualitative research design with a mathematical modeling approach was employed, encompassing problem identification, mathematical model formulation, model solution, and interpretation of results. The findings indicate that residential floor tiling involves multiple geometry concepts aligned with the junior high school curriculum, including area measurement, ratios, unit conversion, estimation, and mathematical decision-making. Variations in tile sizes and materials generate multiple mathematical solutions, encouraging students to engage in critical thinking, compare alternative strategies, and interpret mathematical results within a real-life context. These results demonstrate that floor tiling provides meaningful learning experiences and supports the development of students’ mathematical modeling competencies. This study contributes theoretically to the body of research on mathematical modeling by introducing a familiar real-world context and offers practical implications for teachers in designing contextual and applicable geometry instruction at the junior high school level.